2009 6th IEEE International Working Conference on Mining Software Repositories 2009
DOI: 10.1109/msr.2009.5069480
|View full text |Cite
|
Sign up to set email alerts
|

Tracking concept drift of software projects using defect prediction quality

Abstract: Defect prediction is an important task in the mining of software repositories, but the quality of predictions varies strongly within and across software projects. In this paper we investigate the reasons why the prediction quality is so fluctuating due to the altering nature of the bug (or defect) fixing process. Therefore, we adopt the notion of a concept drift, which denotes that the defect prediction model has become unsuitable as set of influencing features has changed-usually due to a change in the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 13 publications
0
34
1
Order By: Relevance
“…Hence, we do not seem to have any timeshifting effects in these datasets. A finding we find surprising given our previous work [4], [30].…”
Section: B Influence Of Process Quality On Product Qualitycontrasting
confidence: 63%
“…Hence, we do not seem to have any timeshifting effects in these datasets. A finding we find surprising given our previous work [4], [30].…”
Section: B Influence Of Process Quality On Product Qualitycontrasting
confidence: 63%
“…Area under curve (AUC) is also a robust measure to assess and compare the performance of classifiers [26]. For example, using "accuracy" as a measure of prediction is problematic in heavily skewed distributions since it does not relate the prediction to the probability distribution of the classes, but AUC is insensitive to probability distributions [21]. In many situations, a proposed approach (e.g., a classifier) may be superior to the baselines for some input data but not for others.…”
Section: Comments From 5 Papers]mentioning
confidence: 99%
“…Ekanayake et. al revealed that useless phase exists in defect prediction using the notion of concept drift, which invalidates a learned prediction model [63]. As history data is a good predictor of future bugs in the stable phase, however, in unstable phase, it is not the case, resulting in reducing the effectiveness of future effort and resource allocation.…”
Section: Purpose Of Msr Analysismentioning
confidence: 99%